Associations between inflexible job conditions, health and healthcare utilisation in England: retrospective cross-sectional study. Issue 12 (5th December 2022) - Moss, Charlie; Munford, Luke Aaron; Sutton, Matt
Abstract : Objectives: To estimate the strength of association between having an inflexible job and health-related quality of life and healthcare utilisation; and to explore heterogeneity in the effects by gender, age and area-level deprivation. Design: Retrospective cross-sectional study. Setting: Seven waves of the English General Practice Patient Survey between 2012 and 2017. Participants: 1 232 884 people aged 16–64 years and in full-time employment. We measured job inflexibility by inability to take time away from work during usual working hours to seek medical care. Primary and secondary outcome measures: Health-related quality of life (EQ-5D-5L); number of months since the respondent last saw a general practitioner (GP) or nurse; use of out-of-hours general practice in the past 6 months. We used regression analyses to estimate the strength of association between outcomes and having an inflexible job, adjusting for person and area-level characteristics. Results: One-third of respondents reported job inflexibility. The probability of job inflexibility was higher at younger ages and in more deprived areas. Job inflexibility was associated with lower EQ-5D-5L utility scores of 0.017 (95% CI 0.016 to 0.018) for women and 0.016 (95% CI 0.015 to 0.017) for men. Women were more affected than men in the mental health domain. The reduction in health-related quality of life associated with having an inflexible job was greater for employees who were older or lived in more deprived areas. Having an inflexible job was associated with a longer time since the last visit to their GP of 0.234 (95% CI 0.201 to 0.268) months for women and 0.199 (95% CI 0.152 to 0.183) months for men. Conclusions: Inequalities in the prevalence of inflexible jobs contribute to inequalities in health. One mechanism may be through reduced access to healthcare. Policymakers and employers should ensure that all employees have sufficient job flexibility to protect their health.